2013
DOI: 10.1080/0951192x.2012.749531
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art cryogenic machining and processing

Abstract: This paper is a state-of-the-art review of the use of cryogenic cooling using liquefied gases in machining. The review is classified into two major categories namely, cryogenic processing and cryogenic machining. In cryogenic processing also known as cryo-processing the cutting tool material is subjected to cryogenic temperatures as a part of its heat treatment process. The majority of the reported studies identify that cryo-processing can considerably increase cutting tool life especially for high speed steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(76 citation statements)
references
References 123 publications
0
72
0
4
Order By: Relevance
“…smoother surface topography, increasing hardness on the surface and generated compressive residual stress. Besides, the state of the art on cryogenic processing and machining was recently summarized by Shokrani et al [203].…”
Section: Cryogenic Machiningmentioning
confidence: 99%
“…smoother surface topography, increasing hardness on the surface and generated compressive residual stress. Besides, the state of the art on cryogenic processing and machining was recently summarized by Shokrani et al [203].…”
Section: Cryogenic Machiningmentioning
confidence: 99%
“…Shokrani et al [2] have studied the effect of cryogenic cooling in machining operations and concluded that milling and drilling operations with different work tool combinations could be attempted. The difficulty lies in machine materials like titanium having low thermal conductivity and has high localized temperatures present at the cutting zone.…”
Section: Introductionmentioning
confidence: 99%
“…Direct application of cryogen in the cutting zone can reduce the coefficient of friction between sliding surfaces, reduces the cutting forces, increase the hardness of work piece and cutting tool, and lower down the welding tendency of tool and work piece material [24]. In this respect, Dhananchezian et al [25]performed the cryogenic machining of a ferrous alloy using WC inserts.…”
Section: Introductionmentioning
confidence: 98%